Assessment of groundwater quality in terms of organic matter content at water intakes in Środa Wielkopolska - Zimoch, Izabela; Górska, Aleksandra; Weber, Łukasz (Instal, 2024)
Groundwater, as a source of supply for residents, requires a multifaceted analysis in the context of assessing and managing its quality. A particular challenge is the monitoring and analysis of the properties of tertiary groundwater intakes, which are characterized by high content of organic substances. This translates into intense coloration and a significant potential for forming by-products during disinfection processes. This article presents a review of the literature, analysis of selected cases, and results of groundwater quality research in a tertiary intake for the city of Środa Wielkopolska. The tertiary groundwater complex is located in layers with a complex geological structure and is characterized by complicated hydrogeological relationships. A key factor influencing the usable state of water in the discussed intake is the geological structure of the area. Predominantly, layers of lignite directly overlying the aquifer, as well as clays and silts, dominate this area. Particular attention was paid to the analysis of the impact of the thickness of these geological layers on the quality of water obtained from individual wells and the hydrogeological conditions of the exploited deep wells, with special consideration of their efficiency. The correlation was established based on the geological cross-sections of 17 exploited deep wells as well as hydraulic data as part of the water supply system (SZW) of Środa Wielkopolska. For assessing the organic matter content, in addition to typical indicators such as colour, total organic carbon (TOC), dissolved organic carbon (DOC), permanganate index, and UV absorbance, biodegradable dissolved organic carbon (BDOC) was also used, which is helpful in determining the amount of organic compounds that could potentially be a source of carbon and energy, supporting the growth and development of bacteria in the water supply network. Mutual correlations of various indicators were checked, while also establishing the usefulness of simple analyses (UV absorbance or permanganate index) in assessing the level of substances designated as TOC or DOC.